Philippine Literature in Spanish in the Context of Transoceanic Studies: from the Philippines to Spain and Back (19th and 20th centuries) - Ortuño Casanova, Rocío (TSN. Transatlantic Studies Network, 2025)
Despite the narrative that insists that Fil-Hispanic literature is forgotten in Spain, the fact is that since the second half of the 19th century there have been moments of great Philippine presence in the Spanish cultural field. Some metrics are used to establish these moments of great production written in Spanish about the Philippines and the reasons for these peaks are explained, what works have been published in these years and what dialogues have been established with Spain and with America. In general, it is established that the cultural production around the Philippines is closely linked to historical events that concern both nations, Spain and the Philippines, very present in the Spanish press at each moment and that the publishing market has been able to take advantage of these events to publish Philippine works or works about the Philippines. In addition, it is explained that, although the transnational nature of Spanish-Philippine literature has kept it away from Spanish-language literary studies, this same transnational nature has aroused great interest among researchers in the last two decades.